A Minimal Functional Complex of Cytochrome P450 and FBD of Cytochrome P450 Reductase in Nanodiscs. Issue 28 (14th June 2018) - Prade, Elke; Mahajan, Mukesh; Im, Sang‐Choul; Zhang, Meng; Gentry, Katherine A.; Anantharamaiah, G. M.; Waskell, Lucy; Ramamoorthy, Ayyalusamy
Abstract: Structural interactions that enable electron transfer to cytochrome‐P450 (CYP450) from its redox partner CYP450‐reductase (CPR) are a vital prerequisite for its catalytic mechanism. The first structural model for the membrane‐bound functional complex to reveal interactions between the full‐length CYP450 and a minimal domain of CPR is now reported. The results suggest that anchorage of the proteins in a lipid bilayer is a minimal requirement for CYP450 catalytic function. Akin to cytochrome‐b5 (cyt‐b5 ), Arg 125 on the C‐helix of CYP450s is found to be important for effective electron transfer, thus supporting the competitive behavior of redox partners for CYP450s. A general approach is presented to study protein–protein interactions combining the use of nanodiscs with NMR spectroscopy and SAXS. Linking structural details to the mechanism will help unravel the xenobiotic metabolism of diverse microsomal CYP450s in their native environment and facilitate the design of new drug entities. Abstract : Solving a structure of the cytochrome P450 (CYP450) complex with its redox partner is a vital prerequisite to understand the selective route of electron transfer. Structural interactions of CYP450‐redox partner complex anchored in lipid membrane are a minimal requirement for functionality (electron transfer). This study unravels the drug/xenobiotic metabolism by diverse microsomal CYPs in their native membrane environment.